Does influenza vaccination increase consultations, corticosteroid prescriptions, or exacerbations in subjects with asthma or chronic obstructive pulmonary disease?. Issue 10 (26th September 2003) - Tata, L J; West, J; Harrison, T; Farrington, P; Smith, C; Hubbard, R
Abstract : Background: Concern over the safety of influenza vaccination in individuals with obstructive airways disease has contributed to suboptimal rates of vaccine uptake in this group. We investigated the safety of influenza vaccine in older people with asthma or chronic obstructive pulmonary disease (COPD) in a cohort from the UK General Practice Research Database (GPRD). Methods: A population based cohort study of 12 000 individuals with asthma or COPD from 432 general practices was conducted. Incidence rate ratios (IRR) were calculated for asthma or COPD diagnoses, prescriptions for oral corticosteroids, and acute exacerbations on the day of vaccination and on days 1–2 and 3–14 after vaccination compared with other time periods in the influenza season. Results: The IRRs for asthma or COPD diagnoses and oral corticosteroid prescriptions were increased on the day of vaccination (for example, the IRR for oral corticosteroid prescriptions for subjects with asthma during the 1992–3 influenza season was 8.24 (95% confidence interval 5.54 to 12.26)). However, there was no consistent increase in the IRR of any of the outcomes on days 1–2 or 3–14 after vaccination, and most of these IRRs were close to 1. Rates of exacerbation were low and showed no consistent statistically significant increase during any risk periods. Conclusions: Older people with asthma or COPD commonly have diagnoses recorded or prescriptions for oral corticosteroids given on the day of influenza vaccination, but there is no increased risk of adverse acute outcomes in the first 2 weeks after vaccination. Our findings strongly suggest that influenza vaccination is safe in this population.